Characteristics of suspended solids affect bifenthrin toxicity to the calanoid copepods Eurytemora affinis and Pseudodiaptomus forbesi. (14th August 2015) - Parry, Emily; Lesmeister, Sarah; Teh, Swee; Young, Thomas M.
Abstract Bifenthrin is a pyrethroid pesticide that is highly toxic to aquatic invertebrates. The dissolved concentration is generally thought to be the best predictor of acute toxicity. However, for the filter‐feeding calanoid copepods Eurytemora affinis and Pseudodiaptomus forbesi, ingestion of pesticide‐bound particles could prove to be another route of exposure. The present study investigated bifenthrin toxicity to E. affinis and P. forbesi in the presence of suspended solids from municipal wastewater effluent and surface water of the San Francisco (CA, USA) Estuary. Suspended solids mitigated the toxicity of total bifenthrin to E. affinis and P. forbesi, but mortality was higher than what would be predicted from dissolved concentrations alone. The results indicate that the toxicity and bioavailability of particle‐associated bifenthrin was significantly correlated with counts of 0.5‐µm to 2‐µm particle sizes. Potential explanations could include direct ingestion of bifenthrin‐bound particles, changes in food consumption and feeding behavior, and physical contact with small particles. The complex interactions between pesticides and particles of different types and sizes demonstrate a need for future ecotoxicological studies to investigate the role of particle sizes on aquatic organisms. Environ Toxicol Chem 2015;34:2302–2309. © 2015 SETAC